Cardiac transplantation as resolution for Uhl's anomaly: A case report - Juan J. Bacigalupe, MD; Natalia Vensentini, MD; Santiago Torroba, MD; Javier A. Mariani, MD; Sandra Defelitto, MD; Norberto Blanco, MD; Fabian Paetz, MD; Julieta Ximena Saenz, MD; Marcelo Nahin, MD; Maximiliano de Abreu, MD (JHLT Open)
Uhl's anomaly is an extremely rare congenital cardiac defect characterized by the absence of myocardium in the right ventricle. It has a poor prognosis, typically fatal during the perinatal period, with very few patients reaching adulthood. We present the case of a 28-year-old woman with heart failure and ventricular arrhythmia associated with Uhl's anomaly, who required cardiac transplantation, with favorable postoperative outcomes. Uhl's anomaly represents an exceedingly rare cause of cardiac transplantation in adults.